THE EFFECTS OF STATIN THERAPY ON PNEUMONIA OUTCOMES - Makharynska, O.; Zhuravka, N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
HMG-CoA reductase inhibitors (statins) are the most prescribed class of drugs in the world. Some authors suggest that positive effects of statins were reported for statins against pneumonia. These positive studies data were counterbalanced by at least one negative prospective cohort study. Where lies the truth? Better understanding the statins influence and their potential role in pathophysiological pneumonia mechanisms is needed because of high quantity of subjects receiving statins with numerous medical conditions significantly associated with increased short-term mortality.